Structural correlates of atypical visual and motor cortical oscillations in pediatric‐onset multiple sclerosis. Issue 15 (10th July 2020) - Waldman, Amy T.; Sollee, John R.; Datta, Ritobrato; Lavery, Amy M.; Liu, Geraldine; Aleman, Tomas S.; Banwell, Brenda L.; Gaetz, William C.
Abstract: We have previously demonstrated that pediatric‐onset multiple sclerosis (POMS) negatively impacts the visual pathway as well as motor processing speed. Relationships between MS‐related diffuse structural damage of gray and white matter (WM) tissue and cortical responses to visual and motor stimuli remain poorly understood. We used magnetoencephalography in 14 POMS patients and 15 age‐ and sex‐matched healthy controls to assess visual gamma (30–80 Hz), motor gamma (60–90 Hz), and motor beta (15–30 Hz) cortical oscillatory responses to a visual‐motor task. Then, 3T MRI was used to: (a) calculate fractional anisotropy (FA) of the posterior visual and corticospinal motor WM pathways and (b) quantify volume and thickness of the cuneus and primary motor cortex. Visual gamma band power was reduced in POMS and was associated with reduced FA of the optic radiations but not with loss of cuneus volume or thickness. Activity in the primary motor cortex, as measured by postmovement beta rebound amplitude associated with peak latency, was decreased in POMS, although this reduction was not predicted by structural metrics. Our findings implicate loss of WM integrity as a contributor to reduced electrical responses in the visual cortex in POMS. Future work in larger cohorts will inform on the cognitive implications of this finding in terms of visual processing function and will determine whether the progressive loss of brain volume known to occur in POMS ultimately contributes to both progressive dysfunction in such tasks as well as progressive reduction in cortical electrical responses in the visual cortex. Abstract : We used magnetoencephalography in 14 pediatric‐onset multiple sclerosis (POMS) patients and 15 age‐ and sex‐matched healthy controls to assess visual gamma (30–80 Hz), motor gamma (60–90 Hz), and motor beta (15–30 Hz) cortical oscillatory responses to a visual‐motor task. 3T MRI was used to: (a) calculate fractional anisotropy (FA) of the posterior visual and corticospinal motor WM pathways and (b) quantify volume and thickness of the cuneus and primary motor cortex. Visual gamma band power was reduced in POMS and was associated with reduced FA of the optic radiations but not with loss of cuneus volume or thickness.